Purchasing Decision Analysis Is Reviewed From Lifestyle, Price Perception And Product Quality - Rima Melati; Rita Tri Yusnita; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to find out the simultaneous and partial influence of Purchasing Decision analysis reviewed from lifestyle, Price Perception and Quality of Xiaomi Mobile Purchase Products in the city of Tasikmalya. The research methods used in this research are descriptive methods of analysis with a survey approach. The population studied was 100 respondents. The data collected is secondary and primary data. The data analysis in this study used Multiple Regression Analysis using SPSS software version 26. The results showed that Lifestyle, Price Perception and Product Quality simultaneously affected xiaomi mobile phone purchase decisions in the city of Tasikmalya. Lifestyle partially affects xiaomi mobile phone purchase decisions in the city of Tasikmalya. Price perception partially affects the decision to purchase xiaomi mobile phones in the city of Tasikmalya. Product quality partially affects the decision to purchase Xiaomi mobile phones in the city of Tasikmalya